Advances in Targeting Insulin-like Growth Factor Signaling Pathway in Cancer Treatment - You, Liangkun; Liu, Changyu; Tang, Hexiao; Liao, Yongde; Fu, Shengling (Current Pharmaceutical Design, 2014)
Insulin-like growth factors (IGFs), along with their receptors and binding proteins, play key roles in human cell proliferation, differentiation and apoptosis. There is now substantial evidence suggesting that the IGF system is involved in the pathogenesis and progression of various malignancies. Recent studies have shown that targeting of the IGF-1 receptor (IGF-1R) signaling pathway might be a novel approach for the treatment of cancer. Presently numerous agents featuring different mechanisms of IGF targeting methods such as IGF-1R monoclonal antibodies, IGF-1R tyrosine kinase inhibitors and IGF ligand specific antibodies are being investigated in more than 170 clinical trials and appear to have potential therapeutic efficacy. However, advanced trials reiterate the importance of predictive biomarkers to guide the clinical efforts of these agents. As a result, current research strategies are emerging to identify the most suitable subpopulations of patients that might benefit from these treatments. Furthermore, newly presented toxicity and growth hormone response and implication of hybrid receptors in IGF signaling pathway pose unprecedented challenges in the design and application of anti-IGF agents. On the other hand, cross-talk in downstream signaling between IGF-1R and other tumor promoting pathways and the development of multi-target agents might encourage the IGF-1R-targeted therapies further into comprehensive treatments of cancer. With both challenges and prospects ahead, this paper reviewed the progress in this particular field.
Keywords: cancer